2018
DOI: 10.3389/fpsyg.2018.01898
|View full text |Cite
|
Sign up to set email alerts
|

Executive Control Deficits Potentiate the Effect of Maladaptive Metacognitive Beliefs on Posttraumatic Stress Symptoms

Abstract: The metacognitive model and recent preliminary research suggests that metacognitive beliefs (i.e., beliefs about thinking) may be particularly important for understanding the pathogenesis of posttraumatic stress (PTS). The metacognitive model also suggests that deficits in executive control (i.e., metacognitive control) may increase the impact of metacognitive beliefs on PTS symptoms. Trauma-exposed adult participants (N = 469), recruited through an online crowdsourcing website, completed a battery of measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 48 publications
3
10
0
Order By: Relevance
“…These findings extend the limited research into the association of metacognitions with PTSD symptoms following a traumatic event (Bardeen & Fergus, 2018;Bennett & Wells, 2010;Fergus & Bardeen, 2017;Halligan et al, 2003;Jelinek et al, 2013;Michael et al, 2007;Takarangi et al, 2017). The results supported the first hypothesis that predicted that high peritraumatic experience would be associated with higher levels of PTSD symptoms.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…These findings extend the limited research into the association of metacognitions with PTSD symptoms following a traumatic event (Bardeen & Fergus, 2018;Bennett & Wells, 2010;Fergus & Bardeen, 2017;Halligan et al, 2003;Jelinek et al, 2013;Michael et al, 2007;Takarangi et al, 2017). The results supported the first hypothesis that predicted that high peritraumatic experience would be associated with higher levels of PTSD symptoms.…”
Section: Discussionsupporting
confidence: 80%
“…These findings align with literature that has established peritraumatic distress and dissociation both as key predictors of PTSD The second and third hypotheses similarly gained support, with participants who reported a high, compared with low, level of either positive or negative metacognitive beliefs about memory reporting higher levels of PTSD symptoms. These findings extend the limited research into the association of metacognitions with PTSD symptoms following a traumatic event (Bardeen & Fergus, 2018;Bennett & Wells, 2010;Fergus & Bardeen, 2017;Halligan et al, 2003;Jelinek et al, 2013;Michael et al, 2007;Takarangi et al, 2017). Notably, whereas past studies suggested that negative metacognitive beliefs had stronger relationships to outcomes (Bardeen & Fergus, 2018;Bennet & Wells, 2010;Fergus & Bardeen, 2017;Jelinek et al, 2013), the present study found similar effect sizes for positive and negative metacognitive beliefs about the memory.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Further, Bennett and Wells (2010) found evidence that metacognitive beliefs about the trauma memory (e.g., the belief that gaps in the memory mean I am not normal), but not memory disorganization within the trauma narrative, positively predicted significant variance in posttraumatic stress symptoms. Further, Bardeen and Fergus (2018) found that deficits in executive control strengthened the positive association between metacognitive beliefs and posttraumatic stress symptoms. Wells (2009) emphasizes that the processes of the CAS are maladaptive in that they increase and maintain threat perceptions and block emotional processing.…”
Section: Introductionmentioning
confidence: 95%